Concrete for tunnel anti-collision wall as well as preparation method and application of concrete

By using new concrete formulas such as carbon mineral mineral materials and hollow glass micro beads, combined with wet grinding grinding and carbon dioxide injection technology, it solves the problem of difficulty absorbing vehicle collision energy for the existing tunnel. The effect of absorption, convenient construction and reducing costs.

CN119330656AActive Publication Date: 2025-01-21CHINA BUILDING MATERIALS ACADEMY CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411292714.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-01-21
Estimated Expiration
2044-09-14

AI Technical Summary

Technical Problem

The existing tunnel anti-collision wall materials are difficult to effectively absorb the impact force of vehicle collisions, resulting in damage to the tunnel structure, and are difficult to construct and high maintenance costs.

Method used

A new type of concrete formula, including cement, carbon mineral materials, hollow glass micro beads, foaming agents, foaming agents, water reducing agents, fiber and sodium bicarbonate aquatic solution as mixing water, grinding and carbon dioxide through wet method and carbon dioxide Injecting technology, improve the energy absorption capacity and construction convenience of materials.

Benefits of technology

This new type of concrete has long-term stable collapse energy absorption, excellent impact toughness and freeze-thaw resistance. It can effectively absorb the energy of vehicle collisions, reduce the risk of tunnel structure damage, simplify the construction process and reduce maintenance and material costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005045081750000051
    Figure BDA0005045081750000051
  • Figure BDA0005045081750000071
    Figure BDA0005045081750000071
  • Figure HDA0005045081760000011
    Figure HDA0005045081760000011
Patent Text Reader

Abstract

The invention relates to the technical field of concrete, and particularly discloses concrete for a tunnel anti-collision wall as well as a preparation method and application of the concrete. The concrete for the tunnel anti-collision wall is prepared from the following components: 180 to 220 parts of cement, 70 to 110 parts of a carbon mineralized mineral material, 10 to 15 parts of hollow glass beads, 1 to 1.6 parts of a foaming agent, 0.4 to 0.7 part of a foam stabilizer, 3 to 9 parts of a water reducing agent, 0.6 to 2 parts of fibers and 130 to 180 parts of mixing water, the preparation method of the carbon mineralized mineral material comprises the following steps: taking 100-300 parts by weight of mineral material and 10-50 parts by weight of water, injecting 20-100% CO2 at the flow rate of 1-3 L / min, and grinding for 20-60 minutes at the speed of 400-600 rpm; and drying to constant weight, smashing and sieving to obtain the traditional Chinese medicine composition. The concrete for the tunnel anti-collision wall has long-term stable collapse energy absorption, and is excellent in impact toughness and freeze-thaw resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of concrete, and in particular to concrete for tunnel crash barriers and a preparation method and application thereof. Background Art

[0002] As an important part of modern transportation infrastructure, tunnels play a vital role in highways, railways and urban transportation networks. With the increase in traffic volume and the increase in vehicle speed, the problem of traffic safety in tunnels has become increasingly prominent. The closed environment and space limitations of tunnels make rescue and evacuation more difficult when a traffic accident occurs. Therefore, preventing vehicles from colliding with tunnel walls and reducing the occurrence of traffic accidents have become one of the important considerations in tunnel design and construction.

[0003] At present, common tunnel anti-collision measures mainly include the installation of anti-collision guardrails, anti-collision piers and anti-collision walls. Traditional tunnel anti-collision walls are usually made of concrete, reinforced concrete or metal materials, and their high strength and durability can resist the impact of vehicle collisions. However, in actual applications, such anti-collision walls have the disadvantages of excessive rigidity, difficulty in construction, high maintenance cost and high material cost.

[0004] In response to the above problems, patent CN108004986B provides a tunnel crash wall template reinforcement system and construction method to solve the quality problems existing in the prior art, such as poor concrete molding quality, irregular corners, and slurry leakage. Patent CN217440044U provides a convenient tunnel crash wall steel template installation and removal device. However, the above invention still uses hard materials such as concrete and steel structure as the crash wall matrix, which is difficult to absorb the impact force of accident vehicles, causing damage to the tunnel structure.

[0005] Therefore, there is an urgent need for a new type of tunnel crash barrier and its preparation method to improve the energy absorption capacity of the crash barrier, simplify the construction process, reduce maintenance costs and material costs, and thus improve the overall safety and economy of the tunnel. Summary of the invention

[0006] In order to overcome the deficiencies in the prior art, the present application provides a concrete for a tunnel crash wall and a preparation method and application thereof.

[0007] In a first aspect, the present application provides a concrete for a tunnel crash wall, specifically comprising the following components in parts by weight: 180-220 parts of cement, 70-110 parts of carbon mineralized mineral materials, 10-15 parts of hollow glass microspheres, 1-1.6 parts of foaming agent, 0.4-0.7 parts of foam stabilizer, 3-9 parts of water reducer, 0.6-2 parts of fiber, and 130-180 parts of mixing water; The mixing water is selected from at least one of a sodium bicarbonate aqueous solution and carbonated water; The preparation method of the carbon mineralized mineral material is: Weigh a total of 100 to 300 parts by weight of mineral materials and 10 to 50 parts by weight of water, and put them into a grinding jar equipped with ball mill beads; inject 20% to 100% CO2 with a CO2 flow rate of 1 to 3 L / min, and start grinding at 400 to 600 rpm for 20 to 60 minutes; then dry to constant weight, pound and sieve to obtain the mineral material; the mineral material is selected from one or more of carbon-mineralized yellow phosphorus slag, carbon-mineralized carbide slag, carbon-mineralized cement clinker, carbon-mineralized steel slag, and carbon-mineralized magnesium slag.

[0008] The present application utilizes the above-mentioned technical scheme to prepare carbon mineralized mineral materials, and by screening and using specific amounts of cement, carbon mineralized mineral materials, hollow glass microspheres, foaming agents, foam stabilizers, water reducers, fibers, and mixing water as raw material components of concrete, the prepared concrete for tunnel crash barriers has long-term stable collapse energy absorption, and excellent impact toughness and freeze-thaw resistance.

[0009] Preferably, the hollow glass microspheres have a particle size of ≤60 μm and a true density of ≤0.6 g / cm 3 .

[0010] Preferably, the foaming agent is hydrogen peroxide with a mass concentration of 10 to 35%.

[0011] In some specific embodiments, the mass concentration of the hydrogen peroxide may be 10-20%, 20-35%.

[0012] In a specific embodiment, the mass concentration of the hydrogen peroxide solution can also be 10%, 20%, or 35%.

[0013] Through experimental analysis, it can be known that the application selects hydrogen peroxide with the above mass concentration as a foaming agent, which can further improve the performance of concrete.

[0014] Preferably, the foam stabilizer is selected from one or more of methyl cellulose ether (MC), hydroxyethyl cellulose ether (HEC), hydroxyethyl methyl cellulose ether (HEMC), hydroxypropyl methyl cellulose ether (HPMC), stearate series foam stabilizers, styrene-butadiene emulsion, and ethylene-vinyl acetate emulsion.

[0015] Furthermore, the foam stabilizer is composed of a mixture of hydroxypropyl methylcellulose ether and styrene-butadiene emulsion in a weight ratio of 7:0.5-1.5.

[0016] Through experimental analysis, it can be known that the present application selects the above-mentioned weight ratio of hydroxypropyl methylcellulose ether and styrene butadiene emulsion to mix and form a foam stabilizer, which can further improve the performance of concrete.

[0017] Preferably, the water reducer is selected from one or more of polycarboxylic acid water reducers and naphthalene water reducers.

[0018] Preferably, the fiber is selected from one or more of polypropylene fiber, polyvinyl alcohol fiber and carbon fiber.

[0019] Preferably, the mixing water is a sodium bicarbonate aqueous solution with a molar concentration of 0.10 to 0.75 mol / L.

[0020] In some specific embodiments, the molar concentration of the sodium bicarbonate aqueous solution can be 0.10-0.25 mol / L, 0.10-0.4 mol / L, 0.10-0.55 mol / L, 0.25-0.4 mol / L, 0.25-0.55 mol / L, 0.25-0.75 mol / L, 0.4-0.55 mol / L, 0.4-0.75 mol / L, 0.55-0.75 mol / L.

[0021] In a specific embodiment, the molar concentration of the sodium bicarbonate aqueous solution can also be 0.10 mol / L, 0.25 mol / L, 0.4 mol / L, 0.55 mol / L, or 0.75 mol / L.

[0022] Through experimental analysis, it can be known that the application selects the sodium bicarbonate aqueous solution with the above molar concentration as mixing water, which can further improve the performance of concrete.

[0023] Based on the above, the inventors of the present application discovered that in the formula system for preparing concrete for tunnel crash barriers, there is mutual selectivity between foaming agents, foam stabilizers, mixing water and carbon mineralized mineral materials, and different types and specifications of raw materials have a great influence on the impact toughness and freeze-thaw resistance of concrete. The present application further improves the performance of concrete by further screening the types and specifications of raw materials for foaming agents, foam stabilizers and mixing water.

[0024] In a second aspect, the present application provides a method for preparing the above-mentioned concrete for tunnel crash wall, which specifically comprises the following steps in sequence: Firstly, cement, carbon mineralized mineral material, hollow glass microspheres and fibers are weighed, and then poured into a mixer and mixed for 10 to 60 seconds until uniform; Add mixing water, foam stabilizer and water reducer, stir at 200-600rpm for 60-600s, then stir at 1000-3000rpm for 10-60s; Add a foaming agent, and stir at a speed of 1000 to 3000 rpm for 10 to 60 seconds to obtain a slurry; Pour the slurry into a mold with a mortise and tenon structure and let it stand for 0.5 to 2 hours to foam; Place it in a curing room for 24 to 48 hours, then demould and continue curing for 28 to 180 days.

[0025] In a third aspect, the present application provides a tunnel crash barrier, which is prepared using the above-mentioned tunnel crash barrier concrete.

[0026] In a fourth aspect, the present application provides a method for preparing the above-mentioned tunnel crash barrier, which specifically comprises the following steps in sequence: transporting the cured tunnel crash barrier concrete to the pre-paving position of the tunnel crash barrier, splicing and assembling modules with mortise and tenon structures, and installing panels on the modules to obtain the tunnel crash barrier.

[0027] In summary, the technical solution of this application has the following effects: Adopt the technical scheme of the present application, the resource utilization efficiency of yellow phosphorus slag and carbide slag is low, the environmental pollution is large, and the shortcomings of cement clinker, steel slag and magnesium slag in the traditional grinding process are large in dust, low in efficiency and high in energy consumption. Adopt the wet grinding of appropriate water-solid ratio and the mode of carbon dioxide injection, under the mechanochemical coupling effect, the particle size of yellow phosphorus slag and carbide slag decreases, and the ion dissolution rate is accelerated, and calcite, aragonite and vaterite type CaCO3 are generated in the carbon mineralization reaction process, these products are overlapped alternately, and serve as reactant, nucleator and inert filler with its larger specific surface area in the hydration process. The mechanochemical coupling effect will destroy the material surface passivation layer and form a new surface for carbon mineralization, further increase the absorption of carbon dioxide from the raw material end, reduce the carbon emission of the building materials industry, and have important environmental significance. In addition, the Ca (OH)2 that is not completely mineralized by carbon in the carbide slag can also improve the further hydration of cement, stabilize the mechanical properties of the matrix.

[0028] The technical solution of the present application uses sodium bicarbonate aqueous solution and carbonated water as mixing water, so that the carbon dioxide absorption effect further increases the absorption amount of carbon dioxide, and the HCO3-rich - / CO3 2- It can accelerate the hydration of the slurry and play a role similar to that of an accelerating setting agent. There is no need to add additional accelerating components. It ensures early strength growth while improving mold utilization efficiency and production efficiency.

[0029] The concrete for tunnel crash barriers prepared by the technical solution of the present application has a crush degree of 0.5-0.6, a collapse strength of 0.30-0.40 MPa, and an impact toughness greater than 6000 J. It can absorb collapse energy stably for a long time according to the design standards, provide the buffering effect required for emergency avoidance of various types of accident vehicles, and ensure the safety of vehicles and personnel.

[0030] The technical solution of the present application produces more excellent technical effects by specifically screening the types and specifications of foaming agents, foam stabilizers and mixing water, which work synergistically with carbon mineralized mineral materials, thereby further improving the freeze-thaw resistance of the prepared concrete.

[0031] The technical solution of the present application provides blocks with mortise and tenon structures, which are convenient for quick splicing and installation, and can be tightly fixed together without the use of additional surface adhesives, thereby reducing engineering costs, improving construction efficiency and the stability of the overall structure. After the tunnel crash barrier is used, it can be directly replaced or repaired, which greatly reduces the cost of use. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a schematic diagram of the tunnel crash barrier of the present application; the figure numbers are: 1-road surface; 2-crash barrier; 3-side wall; 4-top plate. DETAILED DESCRIPTION

[0033] The present application is further described in detail below in conjunction with examples, comparative examples and performance testing experiments. These examples should not be construed as limiting the scope of protection claimed in the present application.

[0034] Yellow phosphorus slag was purchased from Guizhou Phosphate Chemical Plant; carbide slag was purchased from Henan Wuhu Environmental Protection Technology Co., Ltd.; polycarboxylate water reducer was purchased from Jiangsu Subote New Materials Co., Ltd.; polyvinyl alcohol fiber was purchased from Anhui Wanwei Group Co., Ltd.; hydroxyethyl cellulose ether was purchased from Shandong Feicheng Yutian Chemical Co., Ltd.; styrene butadiene emulsion was purchased from Shandong Shengkai Chemical Co., Ltd.; hydroxypropyl methylcellulose ether was purchased from Shijiazhuang Wenyu Wood Cellulose Trading Co., Ltd.; ethylene-vinyl acetate emulsion was purchased from Guangzhou Zhonggao Chemical Co., Ltd. Example

[0035] Examples 1-5 Examples 1-5 respectively provide a concrete for a tunnel crash barrier and a preparation method thereof.

[0036] The difference between the above embodiments is that the amount of each component in the concrete for tunnel crash wall is different, as shown in Table 1.

[0037] The preparation method of the concrete for the tunnel crash wall in the above embodiment is: Preparation of carbon mineralized mineral material: weigh a total of 2000g of mineral material (1500g of carbon mineralized yellow phosphorus slag, 500g of carbon mineralized carbide slag), 250g of water, put into a grinding jar equipped with ball mill beads; inject 50% CO2, the CO2 flow rate is 2L / min, and start grinding at 200rpm for 40min; then dry to constant weight, pound and pass through a 75μm sieve to obtain; First, weigh ordinary silicate cement, carbon mineralized mineral material, hollow glass microspheres (particle size 50 μm, true density 0.5 g / cm 3 ), polyvinyl alcohol fiber, and then pour it into a blender and mix for 40 seconds until it is uniform; Add 0.4 mol / L sodium bicarbonate aqueous solution, water, foam stabilizer (mixed with hydroxypropyl methylcellulose ether and styrene-butadiene emulsion in a weight ratio of 7:1), and polycarboxylate water reducer, stir at 400 rpm for 360 s, and then stir at 2000 rpm for 30 s; A hydrogen peroxide foaming agent with a mass concentration of 20% was added, and the mixture was stirred at a speed of 2000 rpm for 30 seconds to obtain a slurry; The slurry was poured into a 1500mm×500mm×900mm mold with a mortise and tenon structure and allowed to foam for 1 hour; Place it in the curing room for 36 hours, then demould and continue curing.

[0038] Table 1 Amount of each component in concrete for tunnel crash wall in Examples 1-5 Embodiment 6-9 Examples 6-9 respectively provide a kind of concrete for tunnel crash barrier and a preparation method thereof.

[0039] The difference between the above embodiment and embodiment 1 is that the type of mixing water is different, as shown below.

[0040] In Example 6: the stirring water is a 0.10 mol / L sodium bicarbonate aqueous solution.

[0041] In Example 7: the stirring water is a 0.25 mol / L sodium bicarbonate aqueous solution.

[0042] In Example 8: the stirring water is a 0.55 mol / L sodium bicarbonate aqueous solution.

[0043] In Example 9: the stirring water is a 0.75 mol / L sodium bicarbonate aqueous solution.

[0044] The remaining process parameters in the above embodiment are the same as those in embodiment 1.

[0045] Examples 10-14 Examples 10-14 respectively provide a concrete for a tunnel crash barrier and a preparation method thereof.

[0046] The difference between the above embodiment and embodiment 1 is that the types of foam stabilizers are different, as shown below.

[0047] In Example 10: the foam stabilizer is composed of a mixture of hydroxyethyl cellulose ether and styrene butadiene emulsion in a weight ratio of 7:1.

[0048] In Example 11: the foam stabilizer is composed of a mixture of hydroxypropyl methylcellulose ether and ethylene-vinyl acetate emulsion in a weight ratio of 7:1.

[0049] In Example 12: the foam stabilizer is composed of a mixture of hydroxypropyl methylcellulose ether and styrene butadiene emulsion in a weight ratio of 1:7.

[0050] In Example 13: the foam stabilizer is composed of a mixture of hydroxypropyl methylcellulose ether and styrene butadiene emulsion in a weight ratio of 7:0.5.

[0051] In Example 14: the foam stabilizer is composed of a mixture of hydroxypropyl methylcellulose ether and styrene butadiene emulsion in a weight ratio of 7:1.5.

[0052] The remaining process parameters in the above embodiment are the same as those in embodiment 1.

[0053] Comparative Example Comparative Examples 1-5 Comparative Examples 1-5 respectively provide a kind of concrete and a preparation method thereof.

[0054] The difference between the comparative example and Example 1 is that the amounts of the components in the concrete for the tunnel crash wall are different, as shown in Table 1.

[0055] The remaining process parameters in the above comparative example are the same as those in Example 1.

[0056] Comparative Example 6 Comparative Example 6 provides a concrete and a preparation method thereof.

[0057] The difference between Comparative Example 6 and Example 1 is that the preparation method of the carbon mineralized mineral material is different, as shown below.

[0058] In Comparative Example 6: Preparation of carbon mineralized mineral material: weigh a total of 2000 g of mineral material (1500 g of carbon mineralized yellow phosphorus slag, 500 g of carbon mineralized carbide slag), 250 g of water, put into a grinding jar equipped with ball mill beads, and grind at 200 rpm for 40 min; then dry to constant weight, pound and pass through a 75 μm sieve to obtain; The remaining process parameters in Comparative Example 6 are the same as those in Example 1.

[0059] Performance testing After the concrete prepared in the embodiment and the comparative example were cured for 28 days, the crushing degree, shrinkage strength and impact toughness were tested respectively.

[0060] The method for testing the crush degree is: testing and calculation according to the requirements of MH / T 5111-2015.

[0061] The method for testing the collapse strength is as follows: cut a 100mm×100mm×100mm specimen from the test block, dry the specimen to constant weight according to the requirements of MH / T5111-2015, then place the specimen in a cube constraint frame and under the compression rod of the universal testing machine, so that the center line of the specimen coincides with the axis of the compression rod, start the universal material testing machine, record the stress and crush depth during the compression process, and draw the crush curve of each age. This application takes the average value of the stress data at 15 to 45mm on the platform section of the crush curve as the collapse strength.

[0062] The impact toughness test method is: refer to the drop hammer impact method of ACI-544-2R-89 to test and calculate the impact energy consumption.

[0063] Freeze-thaw resistance: According to the provisions of MH / T 5111-2015, the impact toughness of concrete is tested after 25 freeze-thaw cycles.

[0064] Test results: as shown in Table 2.

[0065] Table 2 Performance test results of concrete in the examples and comparative examples Combined with Table 2, by comparing the performance test results of concrete in the embodiment and the comparative example, it can be seen that the concrete prepared by the technical solution provided by the present application has a crushing degree of 0.5-0.6, a shrinkage strength of 0.30-0.40 MPa, an impact toughness greater than 6100 J, and a frost resistance coefficient of the concrete after the freeze-thaw test greater than 0.855.

[0066] By comparing the performance test results of concrete in Examples 1 and 6-9, the present application selects a sodium bicarbonate aqueous solution with a molar concentration of 0.10 to 0.75 mol / L as mixing water, which can further improve the impact toughness and freeze-thaw resistance of the concrete.

[0067] By comparing the performance test results of concrete in Examples 1 and 10-14, the present application selects a foam stabilizer composed of hydroxypropyl methylcellulose ether and styrene butadiene emulsion mixed in a weight ratio of 7:0.5-1.5, which can further improve the impact toughness and freeze-thaw resistance of concrete.

[0068] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.

Claims

1. A concrete for tunnel crash wall, characterized in that: Specifically include the following components by weight: 180-220 parts of cement, 70-110 parts of carbon mineralized mineral materials, 10-15 parts of hollow glass microspheres, 1-1.6 parts of foaming agent, 0.4-0.7 parts of foam stabilizer, 3-9 parts of water reducer, 0.6-2 parts of fiber, 130-180 parts of mixing water; The mixing water is selected from at least one of a sodium bicarbonate aqueous solution and carbonated water; The preparation method of the carbon mineralized mineral material is: Weigh a total of 100-300 parts by weight of mineral materials and 10-50 parts by weight of water, and put them into a grinding jar equipped with ball mill beads; inject 20%-100% CO2 with a CO2 flow rate of 1-3 L / min, and start grinding at 400-600 rpm for 20-60 min; then dry to constant weight, pound and sieve to obtain the mineral material; the mineral material is selected from one or more of carbon mineralized yellow phosphorus slag, carbon mineralized carbide slag, carbon mineralized cement clinker, carbon mineralized steel slag, and carbon mineralized magnesium slag.

2. The concrete for tunnel crash wall according to claim 1, characterized in that: The hollow glass microspheres have a particle size of ≤60 μm and a true density of ≤0.6 g / cm 3 .

3. The concrete for tunnel crash wall according to claim 1, characterized in that: The foaming agent is hydrogen peroxide with a mass concentration of 10-35%.

4. The concrete for tunnel crash wall according to claim 1, characterized in that: The foam stabilizer is selected from one or more of methyl cellulose ether, hydroxyethyl cellulose ether, hydroxyethyl methyl cellulose ether, hydroxypropyl methyl cellulose ether, stearate series foam stabilizers, styrene-butadiene emulsion, and ethylene-vinyl acetate emulsion.

5. The concrete for tunnel crash wall according to claim 4, characterized in that: The foam stabilizer is composed of a mixture of hydroxypropyl methylcellulose ether and styrene butadiene emulsion in a weight ratio of 7:0.5-1.

5.

6. The concrete for tunnel crash wall according to claim 1, characterized in that: The fiber is selected from one or more of polypropylene fiber, polyvinyl alcohol fiber and carbon fiber.

7. The concrete for tunnel crash wall according to claim 1, characterized in that: The mixing water is a sodium bicarbonate aqueous solution with a molar concentration of 0.10-0.75 mol / L.

8. The method for preparing concrete for tunnel crash wall according to any one of claims 1 to 7, characterized in that: Specifically, the following steps are performed in sequence: First, weigh cement, carbon mineralized mineral material, hollow glass microspheres and fibers, then pour them into a mixer and mix for 10 to 60 seconds until they are uniform; Add mixing water, foam stabilizer and water reducer, stir at 200-600rpm for 60-600s, then stir at 1000-3000rpm for 10-60s; Add a foaming agent and stir at a speed of 1000-3000 rpm for 10-60 seconds to obtain a slurry; Pour the slurry into a mold with a mortise and tenon structure and let it stand for 0.5-2 hours to foam; Place it in a curing room for 24 to 48 hours, then demould and continue curing for 28 to 180 days.

9. A tunnel anti-collision wall, characterized in that: The tunnel crash barrier is prepared using the concrete for the tunnel crash barrier as described in any one of claims 1 to 7.

10. The method for preparing the tunnel crash barrier according to claim 9, characterized in that: Specifically, the following steps are performed in sequence: The tunnel crash barrier is transported to a pre-paved position of the tunnel crash barrier with concrete after curing, and the module bodies with mortise and tenon structures are spliced ​​and assembled one by one, and the panels are installed on the module bodies to obtain the tunnel crash barrier.

Citation Information

Patent Citations

  • Tunnel crash wall formwork reinforcement system and construction method

    CN108004986B

  • Portable tunnel anti-collision wall steel formwork mounting and dismounting device

    CN217440044U

  • Method for recovering vanadium element in vanadium-containing steel slag

    CN107287431A

  • Light-weight phase change aerated concrete, building body wall and construction method of building body wall

    CN109516754A

  • Method for preparing non-autoclaved aerated concrete brick by wet grinding and carbon sequestration of carbide slag

    CN115215586A